Remote Conditioning by Rhythmic Compression of Limbs Ameliorated Myocardial Infarction by Downregulation of Inflammation via A2 Adenosine Receptors - Xu, Senlei; Gu, Renjun; Bian, Xiangyu; Xu, Xin; Xia, Xuefeng; Liu, Yuchen; Jia, Chengjie; Gu, Yihuang; Zhang, Hongru (Frontiers in Cardiovascular Medicine, 2022)
Background Remote ischemic conditioning (RIC) is a cardioprotective phenomenon, yet transient ischemia is not a requisite trigger for remote cardioprotection. In fact, RIC is a stimulus compound containing interruption of the blood vessel and tissue compression. In this study, we evaluate the effects of remote tissue compression on infarct size after myocardial infarction and explore its preliminary mechanisms. Methods and Results We used a murine model of myocardial infarction to assess ischemia injury and identified remote conditioning by rhythmic compression on forelimb as a novel cardioprotective intervention. We show that the cardioprotective signal transduction of remote conditioning from the trigger limb to the heart involves the release of adenosine. Our results demonstrate that A2a and A2b receptors are indispensable parts for cardioprotection of remote conditioning, which is linked to its anti-inflammatory properties by the subsequent activation of cAMP/PKA/NF-κB axis. Conclusion Our results establish a new connection between remote tissue compression and cardiovascular diseases, which enhances our cognition about the role of tissue compression on RIC cardioprotection.